Academic-community solidarities in land occupation as an Indigenous claim to health: culturally centered solidarity through voice infrastructures - Elers, Christine; Dutta, Mohan (Frontiers in Communication, 2023)
We explore the role of land in Indigenous theorizing of health, embodied in a land occupation resisting a development project imposed top-down on the community by the local government. The proposed development project of building a stopbank on the Ōroua river sought to alienate Māori from the remnants of land. Embedded within and emergent from a culture-centered academic-community-activist partnership, an advisory group of Māori community members at the “margins of the margins” come together to participate in the occupation of the land to lay claim to their land, which forms the basis for securing their health. This essay describes the occupation, theorizing it as at the root of a decolonizing health intervention emergent from Indigenous struggles for sovereignty (tino rangatiratanga). The voices of the advisory group participants, working in partnership with the academic team, generate video narratives that resist and dismantle the communicative inversions produced by the settler colonial state to perpetuate its extractive interests. This essay wraps up by arguing that decolonizing health communication has to begin with and embed itself in the Indigenous struggle for land.